Modified Calix[4]crowns as Molecular Receptors for Barium. Issue 6 (15th May 2018) - Steinberg, Janine; Bauer, David; Reissig, Falco; Köckerling, Martin; Pietzsch, Hans‐Jürgen; Mamat, Constantin
Abstract: A series of modified calix[4]crown‐6 derivatives was synthesized to chelate the heavy group 2 metal barium, which serves as a non‐radioactive surrogate for radium‐223/‐224; radionuclides with promising properties for radiopharmaceutical use. These calixcrowns were functionalized with either cyclic amide moieties or with deprotonizable groups, and the corresponding barium complexes were synthesized. Stability constants of these complexes were measured by using NMR and UV/Vis titration techniques to determine log K values of >4.1. Further extraction studies were performed to characterize the binding affinity of calixcrowns to radioactive barium‐133. Additionally, the ligands containing cyclic amides were investigated regarding their rotational barriers by using temperature‐dependent NMR measurements. Abstract : Catching the barium : The complexation of basket‐like molecules such as functionalized calix[4]crowns with deprotonizable groups leads to the effective binding of heavy group 2 metal ions.